A triple antimicrobial regimen for multidrug-resistant Klebsiella pneumonia in a neonatal intensive care unit outbreak: A case series - Ghaziaa Alanezi; Alaa Almulhem; Marwh Aldriwesh; Manal Bawazeer (Elsevier, 2022)
Gram-negative bacteria are the major pathogens detected in neonatal intensive care units. In the last few years, outbreaks of multidrug-resistant (MDR) Klebsiella pneumonia have become a major health concern, especially given this population's limited antimicrobial choices. In the present case series, we report the effectiveness of using a combination of three antimicrobials (amikacin, colistin and meropenem) for the rapid eradication of MDR K. pneumonia in five septic neonates. One neonate (20%) died due to recurrent episodes of sepsis. The remaining four (80%) neonates recovered completely from sepsis. In conclusion, the triple regimen of amikacin, colistin and meropenem was effective in treating neonatal sepsis caused by MDR K. pneumonia. The findings of the present report propose that a combination of antimicrobial chemotherapies could be further explored in the fight against MDR bacterial isolates.